COVID-19 Incidence in Patients With Immunomediated Inflammatory Diseases: Influence of Immunosuppressant Treatments - Soldevila-Domenech, Natalia; Tío, Laura; Llorente-Onaindia, Jone; Martín-García, Elena; Nebot, Pau; Torre, Rafael de la; Gurt, Alba; Maldonado, Rafael; Monfort, Jordi, the Covidmar Study Group (Frontiers in Pharmacology, 2020)
The effects of immunosuppressant treatments on the incidence of coronavirus disease (COVID-19) remains largely unknown. We studied the effects of the pre-exposure to disease-modifying antirheumatic drugs (DMARDs) that decrease immunological responses on the incidence of COVID-19 to explore the possible effects of these treatments in early manifestations of the disease. For this purpose, we performed a cross-sectional study including 2,494 patients with immunomediated inflammatory diseases (IMIDs) recruited at the outpatient Rheumatology, Dermatology and Gastroenterology services of Hospital del Mar. The primary outcome was the clinical diagnosis of COVID-19 performed by a physician at the hospital or at the primary care centre, from the 1st to the 29th of March 2020. Multivariable Poisson regression models were fitted to estimate COVID-19 relative risk (RR) adjusted by comorbidities. We revealed that biological (RR=0.46, CI95%=0.31- 0.67) and synthetic (RR=0.62, CI95%=0.43-0.91) DMARDs used in IMIDs diminished the incidence of COVID-19. Striking sex differences were revealed with anti-TNFα compounds (RR=0.50, CI95%=0.33-0.75) with higher effects in women (RR=0.33, CI95%=0.17-0.647). Treatment with low glucocorticoid doses also revealed sex differences decreasing the incidence of COVID-19 predominantly in women (RR=0.72, CI95%=0.42-1.22). Our results report a decrease incidence of COVID-19 in a patients receiving specific DMARDs with different immunodepressor mechanisms with striking sex differences. These results underline the interest of repurposing specific DMARDs for the possibility of minimizing the severity of disease progression in the early stages of COVID-19.